Polymer nanocomposites part 1: Structural characterization of zinc oxide nanoparticles synthesized via novel calcination method. (September 2015) - Awad, A; Abou-Kandil, Ahmed I; Elsabbagh, I; Elfass, M; Gaafar, M; Mwafy, E
Zinc oxide (ZnO) is a very important compound used in different industries. Several methods are currently used to synthesize ZnO. In this study, we discuss a novel chemical route used to synthesize and purify ZnO in the nanometer scale, with full control on the particle size. The resultant product is chemically and physically characterized using high-resolution X-ray diffraction, thermal analysis, spectral analysis, and ultrasonic measurements in order to determine the crystallite size and the chemical composition of the product as well as to confirm the absence of impurities. Electron microscopy (scanning and transmission) is used to confirm the particle size of the resultant material and confirm particle size uniformity and absence of agglomeration.